Investigation of Creep Behavior of CNT Reinforced Ti6Al4V Under Dynamic Loads - (:unkn) unknown (CHEM SOC PAKISTAN, 2020)
This study investigates the effects of addition of Carbon nanotube (CNT) at different volume ratios (0.5- 5%) into Ti6Al4V matrix by mechanical alloying in terms of the density, microstructure, hardness and creep under dynamic load. As a result of the good bonding of carbon nanotubes powders with the main matrix, Ti-6Al-4V/CNT composites have experienced change both in microstructure and mechanical properties (such as hardness, density) and, correspondingly, qualitatively creep behaviour of Ti-6Al-4V matrix alloy has been improved compared to the lean one. The density of CNT reinforced Ti6Al4V composites sintered at 1300 degrees C for 3h decreases with increasing CNT content. The hardness tests indicated that the hardness of composites increased with CNT addition. In addition, although creep strain is decreased continually with CNT content until 5%, creep life increased with increasing CNT content until 4% of CNT but decreased above 4%. After sintering at 1300 degrees C under vacuum for 3 hours the density of the composite material reached to a level of 98.5 %, the microhardness to 538 HV and the creep behaviour was improved. The characterization of Ti6Al4V/CNT composites after mechanical alloying was carried out using scanning electron microscopy (SEM), energy dispersive x-rays spectroscopy (EDS) analysis and X-ray diffraction (XRD) methods. Although Ti-6Al-4V alloys are used as biomaterial, this study aimed at using MWCNTs containing Ti-6Al-4V composites at high temperature applications. Because MWCNTs reinforced Ti-6Al-4V composites are cheaper and have lower weight than the other materials used in this kind of applications.
Keywords: Dynamic creep; Carbon nanotubes; Sintering; Ti6Al4V; NANOTUBE-POLYMER COMPOSITES; CARBON NANOTUBES; MECHANICAL-PROPERTIES; MATRIX COMPOSITES; TI-6AL-4V; ALLOY